(NkIPENIE (B/s - (NpRISNQKOW(B, (NwLADIMIR fEDOROWI^(B.s; (NkOWALENKO(B, (Nn(B.(Nd(B.s ((NkIEW (B:s (NnAUKOWA DUMKA(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 226-238 (284 (NNAZW(B.)s
(Nan ussr(B, (NiN(B-(NT GEOTEHN(B. (NMEHANIKIs
Keywords: (NkIPENIEs